Building Transversal Solidarities in European Cities: Open Harbours, Safe Communities, Home. (September 2021) - Ataç, Ilker; Rygiel, Kim; Stierl, Maurice
Over the past years, we have seen a rise in political mobilisations in EUrope and elsewhere, by and in solidarity with migrant newcomers. This article focuses on specific examples of what we conceptualise as transversal solidarities by and with migrants, and rooted in the city, the focus of this special issue. The examples we explore in this article include: Trampoline House, a civil society organisation which provides a home to migrant newcomers in Copenhagen; Queer Base, an activist organisation in Vienna providing support for LGBTIQ (Lesbian, Gay, Bisexual, Transgender, Intersex and Queer) migrants; and finally, the Palermo Charter Process, a coalition of diverse groups seeking to create open harbours and 'corridors of solidarity', from the Mediterranean to cities throughout EUrope. While these examples are situated in and across different urban spaces, they share a common grounding in building solidarity through spaces of encounters related to ideas of home, community, and harbour . By exploring these distinct solidarity initiatives in tandem, we examine, on the one hand, how the production of spaces of encounters is linked to building transversal solidarities and, on the other, how transversal solidarities also connect different spaces of solidarity across different political scales.